Ascertaining Household-Level Exposure to Air Pollution: Socio-Demographic Patterning and Urban-Rural Differences in People with Schizophrenia and Other Psychotic Disorders and the General Population - Christoforou, Ella; Lyons , Jane; John , Ann; Fry, Rich; Clift , Martin J.D.; Mizen, Amy (International Journal of Population Data Science, 2026)
Background People with severe mental disorders, including schizophrenia, experience worse physical health and shorter life expectancy. While socio-demographic factors are well established contributors to these disparities, less is known about how environmental exposures differ between individuals with severe mental disorders and the general population. Objective To explore socio-demographic and environmental differences between the general population and individuals with schizophrenia and/or other psychotic disorders (OPD). Methods Anonymised general practice records (2016--2019) for individuals resident in Wales were accessed within the Secure Anonymised Information Linkage (SAIL) Databank. This anonymised health data were linked to small-area level air pollution data for 2016 (PM10, PM2.5, NOx) for individuals who remained at the same residential address during the study period. Individuals with a first relevant diagnosis were identified; age, sex, urban/rural residence, deprivation, and air pollution exposures were compared with the general population. Results Overall, 0.1% (1,784) of the SAIL population had a first recorded diagnosis of schizophrenia/OPD. Of these, 52.7% (941) were male and 47.3% (843) were female. The psychiatric cohort had a higher mean age at study entry than the general population (46.9 vs 42.3 years). The distribution of diagnoses in urban (72.3%) and rural (27.7%) areas closely matched the total population (urban 70.5%, rural 29.5%). Mean air pollutant levels (PM10, PM2.5, NOx) in 2016 were similar between the psychiatric cohort and the general population. A clear socioeconomic gradient was observed: 29.1% of cases resided in the most deprived quintile compared with 15.0% in the least deprived quintile. Conclusions Area-level deprivation was associated with higher prevalence of schizophrenia/OPD, whereas no clear differences were observed by urbanicity or air pollution exposure. Linked population-scale health and environmental data provide valuable evidence which could inform service planning and targeted public health interventions.